2022
DOI: 10.1002/1348-9585.12342
|View full text |Cite
|
Sign up to set email alerts
|

A prospective cohort study of presenteeism and poverty among Japanese workers during the COVID-19 pandemic

Abstract: Objectives This study examined the association of presenteeism with experiences of poverty among Japanese workers during the COVID‐19 pandemic. Methods A prospective cohort study of Japanese workers was conducted using an Internet monitoring survey. The baseline survey was conducted in December 2020, and a follow‐up survey in December 2021. Of the 27 036 workers who participated, 18 560 (68.7%) completed the follow‐up survey. The 11 081 who reported that they were not i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The association between frequent meetings with colleagues and a recent history of COVID-19 suggested that some asymptomatic or minimally symptomatic individuals had transmitted SARS-CoV-2. 14 Moreover, presenteeism, which is common in workplaces as well as among those living in poverty in Japan, 15 may increase the risk of COVID-19. Presenteeism has frequently been observed among healthcare workers even before the start of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The association between frequent meetings with colleagues and a recent history of COVID-19 suggested that some asymptomatic or minimally symptomatic individuals had transmitted SARS-CoV-2. 14 Moreover, presenteeism, which is common in workplaces as well as among those living in poverty in Japan, 15 may increase the risk of COVID-19. Presenteeism has frequently been observed among healthcare workers even before the start of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Covariates at the baseline included age (four quintile), sex (binomial), educational attainment (college graduate or higher), marital status (married, unmarried, or widowed/separated), 22 having children (binomial 14 ), smoking habits (never, past, current), drinking habits (never, past, current), and having more than one underlying diseases (binomial) from hypertension, diabetes, asthma, bronchitis/pneumonia, atopic dermatitis, periodontitis, angina pectoris, cardiac infarction, cerebral vascular disease, chronic obstructive pulmonary disease, malignancy, chronic back pain, depression, and any other psychiatric disease 41 . Equivalent household income (four quintile 42 ), employment status (employer and self-employed, regular employee, others including nonregular employee), fear of Coronavirus-2019 Scale (FCV-19; four quintile), and mean effective reproduction number of COVID-19 in the month before the survey were considered for each prefecture as time-varying covariates 43,44 . The Japanese version of the FCV-19 was validated in previous studies 45 .…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1 shows the study flow. Table 1 shows respondents characteristics: the median age (interquartile range) was 42 (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49) years; the proportion of women was 42.3% (1494); a total of 1020 desk workers (28.9%) had started working from home since or after April 2020; the proportion of desk workers working from home once a week or less, and two to three times a week or more in 2021 was 9% (319/3532) and 14.5% (513/3532), respectively, while in 2022, it was 8.4% (298/3532) and 13.8% (489/3532), respectively. Figure 2 depicts the transition of the work-from-home status.…”
Section: Participants' Characteristicsmentioning
confidence: 99%
“…At baseline, we identified the workers' health conditions by asking them about symptoms known to be strongly associated with presenteeism in previous studies: "Which of the following is closest to the health problem that is most affecting your work?" They answered by selecting one of the following options: "No particular problems"; "Pain"; "Physical movement and mobility"; "Fatigue, loss of strength or appetite, fever, dizziness, and moodiness"; "Toileting and defecation"; "Mental health"; "Skin, hair, and cosmetic concerns"; "Sleep"; "Eye-related matters"; "Nasal matters"; "Hearing"; or "Other" 25 .…”
Section: Explanatory Variablesmentioning
confidence: 99%